Implementation and analysis of integration GSM/GPRS modem in a TMS320VC6713 digital signal processor for Vehicle Location - Hasliza, A. Rahim; R. Badlishah, Ahmad. Dr.; 'Aini Syuhada, Md Zain; U. U., Sheikh (Institute of Electrical and Electronics Engineers (IEEE), 2011)
Link to publisher's homepage at http://ieeexplore.ieee.org/